2019
DOI: 10.1111/sum.12490
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil macropores: Superposition of the roles of organic nutrient amendments and the greenhouse pattern in vegetable plantations

Abstract: Organic farming can potentially mitigate soil compaction, which commonly occurs in vegetable plantations, particularly in greenhouses when compared with open-air systems. Although several studies have addressed the effect of planting patterns on soil pore characteristics, few studies have focused on changes in pore attributes under organic fertilization. We used adjacent fields during green manure planting as a control to compare the differences in soil physicochemical and macropore parameters between 14-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Therefore, the implication of this study is that addition of organic amendments with high C:N will reduce GN via improving soil microbial NO 3 − assimilation (Cheng et al, 2017), and thus reduce the risk of N leaching and runoff from soil (Zhang, Zhu, et al, 2013). However, it should not be neglected that application of organic amendments, a common practice to lessen soil compaction, would reduce soil bulk density (Xu et al, 2019), thereby stimulating gross N mineralization (Elrys et al, 2021) and ultimately increase GN.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the implication of this study is that addition of organic amendments with high C:N will reduce GN via improving soil microbial NO 3 − assimilation (Cheng et al, 2017), and thus reduce the risk of N leaching and runoff from soil (Zhang, Zhu, et al, 2013). However, it should not be neglected that application of organic amendments, a common practice to lessen soil compaction, would reduce soil bulk density (Xu et al, 2019), thereby stimulating gross N mineralization (Elrys et al, 2021) and ultimately increase GN.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with open-air systems, the use of organic fertilizers for indoor greenhouse soils may have a greater positive influence on soil functionality due to its effect on porosity and pore connectivity (Xu et al, 2019). It should be noted that organic fertilizers may not increase crops yields to the levels achievable with inorganic fertilizers.…”
Section: Soil Organic Carbonmentioning
confidence: 99%
“…Different types of macropores have various functions which are related in different ways to the physical (Singh et al, 2021) and chemical properties of the soil. Xu et al (2019) found that soil organic matter increased the total soil porosity, and the volume of both the small and medium size pores. Hu et al (2016) wrote that the variability in the transfer of soluble substances affects soil voids and cracks between the soil aggregates, which increases the volume of soil porosity.…”
Section: Introductionmentioning
confidence: 93%